Students’ perspective on distance learning during Covid-19 pandemic at one state school in Sintang - Oktovianus Mahendra; Sijono Sijono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samudra, 2022)
The background in this study was that the implementation of distance learning using the assignment system in one state school in Sintang did not go well. The study aimed to gain students' perspectives on distance learning and to find challenges and difficulties in the teaching-learning process. The subjects of this study were students of class VIII and IX, totaling 60 students with the object being studied is the student's view. The method used in this research is the qualitative method. The data obtained from the questionnaire showed that more than 90% of students gave a negative response to distance learning. The results of interviews which became supporting data in this study also showed that distance learning was not carried out smoothly and effectively because students were not interested in participating in learning and experienced many difficulties in distance learning. It can be concluded that distance learning using the assignment method during the Covid-19 pandemic did not have a positive impact for students in this school.